From state weakness as strength to state weakness as weakness: Welfare corporatism and the private use of the public interest - Wolfgang Streeck (Max Planck Institute for the Study of Societies, 2003)
The paper is a contribution to a book edited by Simon Green and Willie Paterson, Semi-sovereignty Revisited: Governance, Institutions and Policies in United Germany. The book will appear in 2003 or 2004. It explores to what extent Peter Katzenstein's seminal study of the semi-sovereign German state in the 1980s is still valid. The paper looks at one of the showpieces of Katzenstein's theory of beneficial semi-sovereignty, German industrial relations, and follows their development from the Modell Deutschland of the 1976 election campaign to Schröder's Bündnis für Arbeit. It comes to the conclusion that as far as Germany is concerned, the days are gone when it was an advantage for the governance of industrial relations to have a weak state. – – Das Papier ist ein Kapitel in dem von Simon Green und Willie Paterson herausgegebenen Buch Semi-sovereignty Revisited: Governance, Institutions and Policies in United Germany, das 2003 oder 2004 erscheinen soll. Das Buch untersucht, inwieweit Peter Katzensteins epochemachende Studie über den halbsouveränen deutschen Staat noch Gültigkeit hat. Das Papier behandelt eines von Katzensteins wichtigsten Beispielen für die Vorteile begrenzter staatlicher Souveränität, die Arbeitsbeziehungen. Es verfolgt die Entwicklung der deutschen Arbeitsbeziehungen von Modell Deutschland aus dem Wahlkampf von 1976 bis hin zum Schröderschen Bündnis für Arbeit. Dabei kommt es zu dem Schluss, dass, zumindest was Deutschland angeht, die Tage vorbei sind, als eine schwache Regierung für die Regulierung der Arbeitsbeziehungen von Vorteil war.
Keywords: 300